Synthesis, characterization and Hirshfeld surface analysis of 2-aminobenzothiazol with 4-fluorobenzoic acid co-crystal - Banerjee, Bubun; Sharma, Varun; Sharma, Aditi; Kaur, Gurpreet; Gupta, Vivek Kumar (European Journal of Chemistry, 2022)
The co-crystal of 2-aminobenzothiazol with 4-fluorobenzoic acid were synthesized and characterized by elemental analyses, spectral studies (FT-IR, NMR, HRMS) and single-crystal X-ray diffraction analysis. This compound co-crystallizes in the monoclinic space group P21/c (no. 14), a = 11.7869(14) Å, b = 4.0326(5) Å, c = 27.625(3) Å, β = 92.731(10)°, V = 1311.6(3) Å3, Z = 4, T = 293(2) K, μ(CuKα) = 2.345 mm-1, Dcalc = 1.470 g/cm3, 3568 reflections measured (7.508° ≤ 2Θ ≤ 134.202°), 2280 unique (Rint = 0.0262, Rsigma = 0.0413) which were used in all calculations. The final R1 was 0.0446 (I > 2σ(I)) and wR2 was 0.1274 (all data). The crystal structure is stabilized by elaborate system of N–H···O and O-H···O hydrogen bonds to form supramolecular structures. Furthermore, the 3D Hirshfeld surfaces and the associated 2D fingerprint plots have been analyzed for molecular interactions.